2013
DOI: 10.1371/journal.pone.0058023
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-2-Mediated Protection of Mutant Photoreceptors in Inherited Photoreceptor Degeneration

Abstract: Expression of the Endothelin-2 (Edn2) mRNA is greatly increased in the photoreceptors (PRs) of mouse models of inherited PR degeneration (IPD). To examine the role of Edn2 in mutant PR survival, we generated Edn2−/− mice carrying homozygous Pde6brd1 alleles or the Tg(RHO P347S) transgene. In the Edn2−/− background, PR survival increased 110% in Pde6brd1/rd1 mice at post-natal (PN) day 15, and 60% in Tg(RHO P347S) mice at PN40. In contrast, PR survival was not increased in retinal explants of Pde6brd1/rd1; Edn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 64 publications
7
40
0
Order By: Relevance
“…They suggest that activation of STAT3 signaling pathways is achieved via a 28-fold upregulation of endothelin 2 ( Edn2) which is secreted in response to photoreceptor stress. Once again there are parallels between these findings and studies in the rd1 mouse which have shown retinal upregulation of STAT3 (Samardzija et al 2006) and Edn2 (Bramall et al 2013). This suggests that Stat3 signaling and Edn2 activation act as a potent cell survival response but do not however explain by which step of the active degeneration process they are triggered by.…”
Section: Pde6 Deficiency and Cone Cell Death Mechanismssupporting
confidence: 68%
“…They suggest that activation of STAT3 signaling pathways is achieved via a 28-fold upregulation of endothelin 2 ( Edn2) which is secreted in response to photoreceptor stress. Once again there are parallels between these findings and studies in the rd1 mouse which have shown retinal upregulation of STAT3 (Samardzija et al 2006) and Edn2 (Bramall et al 2013). This suggests that Stat3 signaling and Edn2 activation act as a potent cell survival response but do not however explain by which step of the active degeneration process they are triggered by.…”
Section: Pde6 Deficiency and Cone Cell Death Mechanismssupporting
confidence: 68%
“…ET-2 released from injured photoreceptors may activate Müller cells which subsequently release bFGF, a survival factor of photoreceptors [19,31]. However, ET-2 may also induce bFGF expression in photoreceptors [2]. We found that, in contrast to ET-1, ET-2 osmotic swelling of bipolar cell somata in retinal slices is an indirect effect, likely mediated by ET-1-induced release of swelling-inhibitory factors from Müller cells.…”
Section: Cellular Localization Of Et Receptor Proteinsmentioning
confidence: 65%
“…ET-2 released from injured photoreceptors may activate Müller cells; activated Müller cells produce and release basic fibroblast growth factor (bFGF) which supports the survival of photoreceptors [19,31]. In addition, ET-2 may induce bFGF expression in photoreceptors [2]. In response to photoreceptor injury, Müller cells also produce leukemia inhibitory factor that induces ET-2 in photoreceptors [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the expression of both endothelin-2 and FGF2 is strongly increased in the retina of many IPD and light-damaged models (3,4,7,13), and both have been shown to increase mutant PR survival (4,57,58). Moreover, FGF-2 expression in light-damaged and IPD retinas is regulated by LIF (13,24), and pSTAT3…”
Section: +/Lsl-stat3wtmentioning
confidence: 99%
“…Despite this diversity of genetic etiology, disease progression may be regulated by shared pathways that either promote or resist photoreceptor (PR) death (3). The identification of responses to a PR mutation that are common to many if not most IPDs include the increased expression of endothelin 2 (3,4), accumulation of reactive oxygen species (ROS) (1,5), increased expression of GFAP (3,6,7), and exponential death kinetics (8,9). Some of these common events may have no influence on PR death, but others may represent general pathogenetic or survival responses that influence the rate of PR death, or even dictate it.…”
mentioning
confidence: 99%